2017
DOI: 10.18203/2349-3291.ijcp20171697
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of snake bite in children

Abstract: Background: Snake bite is generally considered to be a rural problem and has been linked with environmental and occupational condition is a neglected public health problem. This study was conducted to ascertain clinical profile, complication and outcome of snake bite in pediatric population. Methods:Retrospective observational study was done in paediatrics wards and Paediatric Intensive care unit of tertiary care institute. A medical record files of 80 patients of snakebite, between the periods of January 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…5,6 Lower limbs were the common site of snake bite this finding corroborates with the work of Jayakrishnan M et al and Jasjit Singh et al 8,9 Regarding time of the bite, it was higher on the evening between 6pm to 6am. This supported by the work of Rajkumar M et al, Meshram et al and Roshini KK et al 10,11 Regarding clinical profile of the patient local pain was present in all patients, oedema at the site of bite was also very common that is 97%, and bleeding from the site of bite was found in 64.28%. This finding is supported by the work of Virendra C et al, Patil et al and Rajesh K et al 12,13 Forty % patients presented with cellulites in our study, this finding in not supported by the study of Khirsagar et al 4 But our study is supported by the work of Virendra C. Patil et al 12 Ptosis was present in 7.3% which is similar to the finding of Rajesh K et al 13 Dyspnoea was present in 14.28% present which nearly collaborates with the finding of Virendra C. Patil et al 12 In present study pain abdomen was found in 11.42% patients of total snake bite patients, this finding was observed by others also Kavitha S et al, found it 10%, but in Rekha Thapar study incidence it was 1.5%.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…5,6 Lower limbs were the common site of snake bite this finding corroborates with the work of Jayakrishnan M et al and Jasjit Singh et al 8,9 Regarding time of the bite, it was higher on the evening between 6pm to 6am. This supported by the work of Rajkumar M et al, Meshram et al and Roshini KK et al 10,11 Regarding clinical profile of the patient local pain was present in all patients, oedema at the site of bite was also very common that is 97%, and bleeding from the site of bite was found in 64.28%. This finding is supported by the work of Virendra C et al, Patil et al and Rajesh K et al 12,13 Forty % patients presented with cellulites in our study, this finding in not supported by the study of Khirsagar et al 4 But our study is supported by the work of Virendra C. Patil et al 12 Ptosis was present in 7.3% which is similar to the finding of Rajesh K et al 13 Dyspnoea was present in 14.28% present which nearly collaborates with the finding of Virendra C. Patil et al 12 In present study pain abdomen was found in 11.42% patients of total snake bite patients, this finding was observed by others also Kavitha S et al, found it 10%, but in Rekha Thapar study incidence it was 1.5%.…”
Section: Discussionsupporting
confidence: 69%
“…13,16 Among all the patient treated with ASV(anti snake venom) only one patient developed reaction to anti snake venom, which corroborates with the finding of Khirsajar et al 4 Acute renal failure was also found in 1.4% of the patient, which corroborates with the finding of Patil B et al 18 Most of the patient treated with ASV and under ICU (intensive care unit) were recovered the percentage of death was 1.5% this is similar to the finding of khirsagar et al, that is 1.81%, as per data of Meshram RM et al, it was 11.25%. 4,10…”
Section: Discussionmentioning
confidence: 99%
“…There was a higher risk of fatalities in victims of snakebite who reported to the hospital after more than six hours of the bite incident, among which majority died within 10 hours of hospitalization [1].…”
Section: Introductionmentioning
confidence: 97%
“…Snakebites are commonly non-provocative in nature and there was a reported higher frequency of incidences during night times [1]. Lower limb was the commonest site of bites [1] as majority of snakebite cases are due to accidental stepping while walking or playing in the dark. Primary treatment includes the administration of antisnake venom and the tetanus toxoid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation